The Influence of Social Media on Global Political Stability: The Mediating Roles of Political Participation, Public Trust, Information Dissemination, and Political Polarization - Nikolas Ethan; Vincent Vincent; Owais Alaric (IHSA Institute, 2026)
This study examines the influence of social media on global political stability by investigating how digital platforms shape political participation, information dissemination, public trust in political institutions, and political polarization within contemporary political systems. The rapid expansion of social media has transformed political communication by increasing citizens' access to information and facilitating civic engagement, while simultaneously creating challenges associated with misinformation, disinformation, ideological polarization, and declining institutional trust. Employing a quantitative research approach with a cross-sectional survey design and a cross-national comparative framework, data were collected from active social media users through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that social media exerts both positive and negative influences on political stability. On the positive side, social media promotes political participation, enhances governmental transparency, and strengthens democratic engagement through improved communication and information accessibility. Conversely, the widespread dissemination of misinformation, the formation of online echo chambers, and increasing political polarization weaken public trust in political institutions and contribute to political instability. These findings suggest that the overall impact of social media depends on contextual factors such as digital literacy, platform governance, regulatory effectiveness, and institutional resilience. This research contributes to the literature on digital political communication by integrating multiple theoretical perspectives into a comprehensive framework and provides practical implications for policymakers, election authorities, technology companies, and civil society organizations in developing strategies to strengthen democratic resilience and promote sustainable political stability in the digital era.